Productivity Growth in the Malaysian Mobile Telecommunications Industry (2004) - Mohamad, Noorihsan (International Islamic University, 2004)
This paper analyzes the changes in productivity of Malaysian mobile telecommunications industry from 1996 to 2001. The data consist of a panel of five mobile service providers in Malaysia, namely Celcom, DiGi, Maxis, TimeCel and TM Cellular. Productivity is measured by the Malmquist index, using a Data Envelopment Analysis (DEA) technique. The Malmquist productivity measures are decomposed into two components: efficiency change and technical change index. The results showed that Total Factor Productivity(TFP) has increased significantly for the whole industry in which technical change has been the most important source of productivity growth to the mobile telecommunications industry. A low level of efficiency change in the industry indicates a great potential for the industry to increase its productivity through higher utilization of technology as well as technological knowledge dissemination. Continuous training programs to familiarize and improve technical expertise appear to offer better prospects for the mobile telecommunications industry to achieve greater productivity growth.